Problematika Guru Dalam Mengolah Raport Kurikulum 2013 Di SD IT Muhammadiyah Al-Kautsar - Kholikh, Abdul; , Minsih, S.Ag, M.Pd (2017)
Raport a report book learning outcomes of students who are administratively reported each semester, all subjects which he passes through. The value entered into the report cards include cognitive value, the value of affective and psychomotor value. This study aims to determine: 1) Processing ratings report cards curriculum, 2013 in SDIT Muhammadiyah Al-Kautsar, 2) The problems experienced by teachers in the process of report cards curriculum, 2013 in SDIT Muhammadiyah Al-Kautsar, 3) Solutions teachers in the process of report cards curriculum, 2013 in SDIT Muhammadiyah Kautsar. This research is a qualitative research with case study design (case studies). The informants are part of the curriculum vice principal, first grade teacher, second grade teacher, third grade teacher, fourth grade teacher, fifth grade teacher, and sixth grade teacher. Data collection techniques used were interviews, observation, and documentation. Data were analyzed through the steps of data collection, data presentation, reduiksi data, and drawing conclusions. Mechanical data validity checking is done by triangulation techniques and triangulation. The results showed the various problems experienced teachers in the process of report cards curriculum, 2013 in SDIT Muhammadiyah Al-Kautsar. Problems experienced teachers in the process of report cards, among others: 1) Master considers that the assessment of the 2013 curriculum is too complicated, 2) Make a description of the achievement in the curriculum report cards in 2013, 3) lack of training in the curriculum report card processing 2013. To overcome this problem, the solution is always training conducted by the Central Government and the socialization of the curriculum in 2013.